2016
DOI: 10.1016/j.jmb.2016.05.028
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation in Cancer Biology: Linking Metabolism and Signaling

Abstract: The Hexosamine Biosynthetic Pathway (HBP) is highly dependent on multiple metabolic nutrients including glucose, glutamine and acetyl-CoA. Increased flux through HBP leads to elevated post-translational addition of β-D-N-acetylglucosamine sugars to nuclear and cytoplasmic proteins. Increased total O-GlcNAcylation is emerging as a general characteristic of cancer cells and recent studies suggest that O-GlcNAcylation is a central communicator of nutritional status to control key signaling and metabolic pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
199
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(202 citation statements)
references
References 95 publications
(217 reference statements)
2
199
0
1
Order By: Relevance
“…Furthermore, glutamine can contribute to the intracellular acetyl-CoA pool as well as to NAD/NADH levels, suggesting a potential role in regulating histone and protein acetylation levels and patterns. Moreover, it has also been shown that UDP-glucosamine (UDP-GlcNAc), used for N-acetylglucosamination (GlcNAcylation) of histones and proteins and can regulate gene expression [88], can be synthesized from glutamine and can also be modulated by it through hexosamine biosynthesis via mTORC2 [89, 90]. …”
Section: Figurementioning
confidence: 99%
“…Furthermore, glutamine can contribute to the intracellular acetyl-CoA pool as well as to NAD/NADH levels, suggesting a potential role in regulating histone and protein acetylation levels and patterns. Moreover, it has also been shown that UDP-glucosamine (UDP-GlcNAc), used for N-acetylglucosamination (GlcNAcylation) of histones and proteins and can regulate gene expression [88], can be synthesized from glutamine and can also be modulated by it through hexosamine biosynthesis via mTORC2 [89, 90]. …”
Section: Figurementioning
confidence: 99%
“…25,26 To date, one of the most remarkable functions for glycosylation is its role in cell adhesion and migration, specifically in cancer metastasis. [27][28][29][30][31] In addition, glycans have been documented for their role in extracellular matrix (ECM) turnover and remodeling in multiple diseases. [32][33][34] Hence, there is a great need for high-throughput technologies to phenotype clinical diseases using glycoanalytic approaches.…”
Section: Metabolism Glycosylationmentioning
confidence: 99%
“…Nearly every cancer type examined to date has elevated levels of O-GlcNAcylation. The review by Ferrer et al [18] describes current findings indicating that O-GlcNAcylation of nucleocytoplasmic proteins is a central sensor and integrator of nutritional status to control important signaling pathways and processes that regulate cancer phenotypes. They summarize how O-GlcNAcylation cycling enzymes change in cancer cells and the various mechanisms by which O-GlcNAc contributes to cancer phenotypes; they alsopoint out the challenges in targeting O-GlcNAcylation that do develop therapeutics.…”
Section: Myriad Roles Of Glycans In Biologymentioning
confidence: 99%